Activation of the B−F Bond by Diphenylcarbene: A Reversible 1, 2‐Fluorine Migration between Boron and Carbon. Issue 7 (10th January 2017) - Costa, Paolo; Mieres‐Perez, Joel; Özkan, Nesli; Sander, Wolfram
Abstract: Experiments in low‐temperature matrices reveal that triplet diphenylcarbene inserts into the very strong B−F bond of BF3 in a two‐step reaction. The first step is the formation of a strongly bound Lewis acid–base complex between the singlet state of diphenylcarbene and BF3 . This step involves an inversion of the spin state of the carbene from triplet to singlet. The second step requires visible‐light photochemical activation to induce a 1, 2‐F migration from boron to the adjacent carbon atom under formation of the formal insertion product of the carbene center into BF3 . The 1, 2‐F migration is reversible under short‐wavelength UV irradiation, thus leading back to the Lewis acid–base adduct. Abstract : In short : Triplet diphenylcarbene inserts into the B−F bond of BF3 molecule by reversible fluorine migration despite a bond dissociation energy of 170 kcal mol −1 . The 1, 2‐F migration is reversible under short‐wavelength UV irradiation.